Analisis Sentimen Komentar YouTube TvOne Tentang Ustadz Abdul Somad Dideportasi Dari Singapura Menggunakan Algoritma SVM - Desti Mualfah; Ramadhoni; Rahmad Gunawan; Danang Mulyadipa Suratno (Unversitas Muhammadiyah Riau, 2023)
Interactions in social media can be seen from comments as feedback from every activity on social media, starting from statuses in the form of text, images or videos. One area of computer technology that can study the meaning of text is text mining. Sentiment analysis or opinion mining is a solution to solving problems to automatically classify opinions into positive and negative. Comments from YouTube video viewers on the TvOne channel about Ustadz Abdul Somad being deported from Singapore. From the various responses in the comment column, information is obtained from unstructured data, so there is a needfor a technique to define the value of information. The focus in this research is to verify the truth and explore the value of structured information so that itcan describe events and topics that are connected from the comments in the YouTube videos which are the object of this research. From the test results above, it can be seen that the performance values from the test results using the Support Vector Machine method get 95.02% Accuracy, 95.02% Recall, 95.18% Precision and 95.01% F1-Score.